Environmental‐related variation of stoichiometric traits in body and organs of non‐native sailfin catfishes Pterygoplichthys spp. Issue 11 (5th November 2022) - Wei, Hui; Liang, Yanting; Luo, Qiang; Gu, Dangen; Mu, Xidong; Hu, Yinchang
Abstract: Intraspecific variation in stoichiometric traits was thought to be an adaptive response to reduce the elemental imbalance between organism and diet in the habitat. Studying the spatial variation of stoichiometric traits of non‐native species and the factors contributing to the variation could help to better understand the invasion mechanism of non‐native fish. In this study, stoichiometric traits (i.e. carbon [C], phosphorus [P], calcium [Ca] and their ratios) variation in the body and organs of non‐native sailfin catfishes Pterygoplichthys spp. were investigated across 13 river sections in the main river basins of Guangdong province. The relationships between environmental factors and stoichiometric traits were analyzed using a general linear model and an information‐theoretic approach. A manipulated feeding experiment was conducted to investigate the impact of food quality on the stoichiometry of sailfin catfishes in a greenhouse. Sailfin catfishes exhibited considerable variability in body and organ elemental composition. Site identity was the main factor contributing to the variation, which could be explained by a combination of environmental factors including climate, diet quality, fish species richness and trophic status in the invaded rivers. Water chemistry (i.e. total nitrogen and phosphorus, ammonia nitrogen and soluble reactive phosphorus) contributed to the most variation of stoichiometric traits. Imbalances of P and Ca between sailfin catfishes and food resources varied among sampling sites, reflecting the spatial heterogeneity of nutrients limitation. Juvenile sailfin catfishes exhibited stoichiometric homeostasis (0 < 1/H < 0.25) for all elemental contents and ratios in the feeding experiment. These findings suggested variation in stoichiometric traits of sailfin catfishes might be attributed to the changes in elemental metabolism to cope with context‐specific environments. This study provided heuristic knowledge about environmental‐related variation in stoichiometric traits, which could enhance the understanding of the non‐native species' adaptation to resource fluctuation in the invaded ecosystems. Abstract : We found sailfin catfishes can exhibit considerable variation in stoichiometric traits in response to the environmental dynamics of the invaded rivers. Water chemistry contributed to the most of variation of stoichiometric traits of sailfin catfishes. Imbalances of P and Ca between sailfin catfishes and food resources varied among sampling sites, reflecting the spatial heterogeneity of nutrient limitation. These findings suggested variation in stoichiometric traits might be attributed to changes in elemental metabolism to cope with context‐specific environments which directly or indirectly affected consumer performance, food resource quality and elemental imbalance.